Women at the Frontlines of Faith: Christian Service and Rural Reconstruction in Wartime Sichuan (Journal for the Study of Religion and History (JSRH), 2025)
This paper investigates how Ginling Women’s College, one of China’s leading Christian institutions for women, engaged in rural reconstruction during the Second Sino-Japanese War. Focusing on its rural service stations in Renshou and Zhonghechang, Sichuan, this paper examines how Christian women educators translated ideals of social service, citizenship, and domestic reform into local practice. Drawing on missionary archives, Guomindang (GMD) administrative documents, and local records, the paper reconstructs both the institutional design and the lived experience of these wartime experiments.Ginling’s initiatives reveal how Christian social work became intertwined with GMD programs of rural reconstruction and moral reform. Through literacy classes, nursery programs, and citizenship training courses, urban-educated women sought to improve rural women’s lives while cultivating civic and moral order. Their efforts exposed tensions between their Christian, urban-informed visions of social improvement and the daily constraints of rural wartime life.By foregrounding everyday encounters between reformers and villagers, this study highlights the social, cultural, and spiritual dimensions of Christian women’s activism. It argues that Ginling’s wartime rural service redefined the relationships among Christian social engagement, gender roles, and the GMD-led reconstruction initiatives, offering new insights into how Chinese Christianity adapted to and participated in the transformation of rural society during the war.
Keywords: Christian social service, Ginling Women's College, wartime reconstruction, rural women, West China